Avaliação do enriquecimento alimentar com itens naturais como ferramenta para conservação do mico-leão-preto (Leontopithecus chrysopygus (Mikan, 1823)) - Santana, Beatriz Cabrera (Universidade Federal de São Carlos, 2020)
The black lion tamarin (Leontopithecus chrysopygus) is at the endangered of extinction and as a conservation strategy we have the ex situ management that aims to maintain a genetic and demographic bank of this species, seeking to reproduce these animals to reintroduce them into their natural environment when necessary and possible. Regarding foraging, the black lion tamarin consumes fruits, exudates, prey and flowers in the natural environment; capturing prey through manipulative foraging. However, the composition and the mode to provide their diet in captivity are different from what would be found in the natural habitat, and to don’t lost the foraging behavior it is necessary to make this aspect closer to the wildlife by food enrichment. Food enrichment decreases abnormal behaviors, stimulates new activities and the expression of the species' natural behavior that favors animal welfare. For this reason, the present study aimed to measure the influence of feeding enrichment on the foraging behavior of the black lion tamarin. To that end, 19 individuals were analyzed in two different environments and we made feeding enrichment by offering items from the natural diet of the species (jerivá fruits and tenebrio beetle) and from the captivity diet (fruits, vegetables and ration) in food enrichments, generating the total of 480 hours behavioral observation divided into 4 situations: without enrichment, with enrichment of the natural diet, with enrichment of the captive diet and with natural and captivity combined enrichment. Were observed 106 behaviors, grouped into 15 categories. In general, the enrichment with greater interaction was with captive items and as the important result it increased affiliation behavior compared to the situation of natural enrichment. Natural enrichment, on the other hand, increased feeding behaviors and decreased stopped behavior. The combination of enrichments with natural items and those of routine items decreased behaviors such as standing, locomotion and physiological categories. In addition, all situations had the interaction with enrichment and the ingestion of enrichment food increased significantly. Therefore, the results show that all the enrichments presented were important to stimulate natural behaviors and to improve the quality animals life, indicating a trend towards animal welfare.
Evaluation of feeding enrichment with natural items as a tool for the black lion conservation (Leontopithecus chrysopygus (Mikan, 1823))
Keywords: Forrageio; Comportamento; Manejo ex situ; Bem-estar animal; Forraging; Behavior; Ex situ management; Animal welfare; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS; CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL